2017
DOI: 10.1017/s0022215116009956
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of osteoradionecrosis

Abstract: The significant financial burden on the health system, and the growing evidence for the effectiveness of pentoxifylline, tocopherol and clodronate, should prompt us to explore this alternative treatment further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…However, fully restoring facial contour and jaw function is extremely complex and not always possible even with modern surgical techniques. Therefore, together with the risk of surgical complications and high costs for society, it is important to investigate the impact of this complex reconstruction procedure on the HRQoL for ORN patients fulfilling the indications for this type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, fully restoring facial contour and jaw function is extremely complex and not always possible even with modern surgical techniques. Therefore, together with the risk of surgical complications and high costs for society, it is important to investigate the impact of this complex reconstruction procedure on the HRQoL for ORN patients fulfilling the indications for this type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not specifically examine the financial cost attributed to managing this patient cohort, the median cost of managing patients with late stage ORN who require resection and free-flap reconstruction among an Auckland, New Zealand cohort was estimated at $105 000 NZD per patient, without factoring in the cost of HBOT. 34 This is $19 000 NZD per patient greater than the cost of managing patients who require free-flap reconstruction surgery for reasons other than ORN. The increased cost of managing ORN patients is likely due to increased rates of post-operative complications as a result of poorer tissue quality and healing due to radiation damage.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates following free flap reconstruction of head and neck ORN are cited between 30%-60% [16,26,44,46,49,50] . While most institutions cite free flap survival rates following head and neck reconstruction as 95% or greater, free flap survival rates following ORN reconstruction are cited at 89-93% [26,46,50,51] . Additionally, it was found that patients undergoing free flap reconstruction for ORN had a higher incidence of late complications compared to patients undergoing free flap reconstruction for malignancy [3] .…”
Section: Surgical Complicationsmentioning
confidence: 99%